Generational dynamics: Eritrean women in Egypt - Hashim, Naseem (AUC Knowledge Fountain, 2012)
This thesis examines the experience of Eritrean women in Egypt across different generations. The purpose of the study is to explore the connection between class, choice and rights in shaping the experiences of three different generations of Eritrean women living in Egypt. This research investigates the experiences of three different groups from Eritrean women in Egypt. The first group is the first generation of Eritrean women who were displaced more than thirty years ago as result of the war between Eritrea and Ethiopia in 1961. The second group is the second generation of Eritrean women who grew up and lived for more than two decades in Egypt. The third group is the new wave of Eritrean women who came to Egypt after the second war between Eritrea and Ethiopia in 1998. One of the main findings of this thesis is that the social exclusion of the first generation did not negatively affect the process of integration into Egyptian society of the second generation. Secondly, the transnational lives that the first generation lived lead the second generation’s rejection of their parents’ transnational marriages. One of the main reasons for the first generation of Eritrean women to choose to come to Egypt was education opportunities for their children. The subsequent new waves of Eritrean women who came to Egypt after the second war in Eretria in 1998 in contrast were driven predominantly by the search for migration opportunities. Some of the new waves of Eritrean women had already acquired Sudanese nationality prior to moving to Egypt, upon arrival they applied for refugee status. In contrast, the second generation of Eritrean women’s the lack of citizenship rights influences their decision to migrate. In general, all three generations are trying to find migration opportunities after the revolution in Egypt.